Economic costs of using tailwater recovery systems for maintaining water quality and irrigation. (1st April 2019) - Omer, A.R.; Henderson, J.E.; Falconer, L.; Krӧger, R.; Allen, P.J.
Abstract: Best management practices (BMPs) are conservation efforts implemented to address environmental challenges associated with agricultural production. One such BMP, a tailwater recovery (TWR) system, has a dual purpose aimed at mitigating solids and nutrient losses from agricultural landscapes and creating an additional surface water source for irrigation. This study analyzes the costs of using five TWR systems to reduce solids, nutrients, and retain water. All systems were located in the Lower Mississippi Alluvial Valley and were used to irrigate crops including rice ( Oryza sativa ), corn ( Zea mays ), and soybeans ( Glycine max ). Costs to reduce solids and nutrients were calculated using annual payments and revenue losses due to lost tillable area from implementation of TWR systems. Similarly, cost to save and irrigate a mega-liter (ML) of water was determined as the annual payment for TWR systems, revenue losses and measured pumping cost. The range of mean total cost to reduce solids using TWR systems was $0 to $0.77 per kg; P was $0.61 to $3315.72 per kg; and N was $0.13 to $396.44 per kg. The range of mean total cost to retain water using TWR systems was $189.73 to $628.23 per ML, compared to a range of mean cost of groundwater of $13.99 to $36.17 per ML. Compared to other BMPs, TWR systems are one of the least expensive ways to reduce solid losses but remain an expensive way to reduce nutrient losses. The costs of using TWR systems to provide an additional irrigation water source range from less expensive than common conservation practices used to improve water use efficiency to more expensive and comparable to practices such as desalination. Therefore, TWR systems may be a prohibitively more expensive BMP to retain nutrients and water on some agricultural landscapes than other solutions. Highlights: Tailwater Recovery (TWR) systems are one of the least expensive practices to mitigate solid losses. Tailwater Recovery systems are one of the most expensive practices to mitigate phosphorus and nitrogen losses. Cost to reduce solids using TWR systems was $0–0.77 per kg; P was $0.61–3, 316 per kg; and N was $0.13–396 per kg. The cost to retain water using TWR systems was $190–628 per ML, compared to a cost of groundwater of $14–36 per ML.